Exercise-mediated IL-6 downstream effects modulate brain pathology–can exercise training protocols influence the downstream effects? - Hezhou Li; Anand Thirupathi (Frontiers in Neurology)
The dual role of interleukin-6 (IL-6) as beneficial in physiological conditions and detrimental in pathological conditions has been a subject of research interest since its discovery. This has surpassed the traditional view of IL-6 as a pro-inflammatory cytokine, primarily due to its multifunctionality. To coordinate this multiple effect, several downstream signaling pathways are involved. Physical exercise mediates these downstream signals and accentuates the pleiotropic effects of IL-6 by enabling cross-talk between various organs, including muscles and the brain. In addition, IL-6 itself is a crucial signaling molecule that enhances exercise performance by maintaining muscle energy homeostasis. However, the specific mechanisms by which this molecule modulates overall brain physiology under different exercise conditions remain unclear. For example, chronic exercise with different exercise protocols could increase chronic plasma levels of IL-6, which could have an impact on brain health. Most studies in the literature have established the beneficial effects of exercise-mediated IL-6, but the impact of chronic elevation of IL-6 by exercise remains unclear. Additionally, the level of IL-6 determines the nature of molecular signaling that underlies all IL-6-mediated functions. This can be achieved by understanding both classic and IL-6 trans-signaling in different physio-pathological conditions. However, the mechanism by which exercise activates these two different classic and IL-6 trans-signaling pathways is less understood. Therefore, this review presents a comprehensive overview of how different exercises mediate IL-6-mediated benefits by discussing the full array of molecular signaling pathways.